2020
DOI: 10.1093/botlinnean/boaa065
|View full text |Cite
|
Sign up to set email alerts
|

Plastome sequencing of a 167-year-old herbarium specimen and classical morphology resolve the systematics of two potentially extinct grass species

Abstract: The systematics of Arundinoideae (Poaceae), a subfamily long considered as a dustbin group, has been progressively resolved in recent decades. The last members incertae sedis of Arundinoideae are two African species not observed for > 150 years and currently studied only on the basis of old herbarium specimens. Based on the sequencing of its whole plastid genome, Leptagrostis schimperiana was placed in the monophyletic Crinipedeae (Arundinoideae) in the grass plastome phylogenetic tree. To date, whole p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…(four species) (Teisher et al, 2017; Hardion et al, 2017). Hardion et al (2021) found close relationships to Crinipes for two potentially extinct monotypic genera, Leptagrostis C.E.Hubb. and Piptophyllum C.E.Hubb., based on plastome and morphological analyses, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(four species) (Teisher et al, 2017; Hardion et al, 2017). Hardion et al (2021) found close relationships to Crinipes for two potentially extinct monotypic genera, Leptagrostis C.E.Hubb. and Piptophyllum C.E.Hubb., based on plastome and morphological analyses, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…(four species) (Teisher et al, 2017;Hardion et al, 2017). Hardion et al (2021) 2017), but that study noted a similarly long stem for this group and argued for a possible East Asian origin of its three or four genera. In our biogeographical analysis, the stem area is Afrotropical (50%), and the probable crown area is Cosmopolitan (68%).…”
Section: Arundinoideae (Jkt)mentioning
confidence: 91%
“…Plastome sequences can offer valuable insights into phylogenetic relationships in plants ( Dong et al, 2012 ; Curci et al, 2016 ). They have been increasingly adopted in phylogenetic studies of Poaceae species due to the rapid development of next-generation sequencing technology ( Saarela and Graham, 2010 ; Burke et al, 2016 ; Duvall et al, 2016 , 2020 ; Guo et al, 2019 ; Orton et al, 2019 ; Liu et al, 2020 ; Welker et al, 2020 ; Hardion et al, 2021 ). Plastomes have been used to study phylogenetic relationships within Eragrostis and Triodia of Chloridoideae ( Anderson et al, 2019 ; Somaratne et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we also analyzed one of the oldest herbarium specimens of Areca collected in Maluku during the Dumont d'Urville's expedition in 1839, andanother collected in Philippines in 1916. This shows how herbarium collections can provide material for phylogenomics studies, and thus facilitate an exhaustive taxa sampling (e.g., Zedane et al 2016;Hardion et al, 2021), especially in remote islands of Wallacea (Strijk et al, 2020).…”
Section: New Genomic Datasets For Investigating Areca Phylogeography ...mentioning
confidence: 95%